2015
DOI: 10.3109/02699206.2015.1079247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blindness on production–perception relationships: Compensation strategies for a lip-tube perturbation of the French [u]

Abstract: The impact of congenital visual deprivation on speech production in adults was examined in an ultrasound study of compensation strategies for lip-tube perturbation. Acoustic and articulatory analyses of the rounded vowel /u/ produced by 12 congenitally blind adult French speakers and 11 sighted adult French speakers were conducted under two conditions: normal and perturbed (with a 25-mm diameter tube inserted between the lips). Vowels were produced with auditory feedback and without auditory feedback (masked n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…Having no access to visual cues, they instead use tongue movements to enhance saliency. Similar results were reported by Trudeau-Fisette et al [ 11 ] and Ménard et al [ 7 ] who showed that sighted speakers primarily used their lips to produce clear speech while blind speakers prioritized the use of their tongue. Thus access to the visual channel affects control of the speech articulators, and consequently the related acoustic targets.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Having no access to visual cues, they instead use tongue movements to enhance saliency. Similar results were reported by Trudeau-Fisette et al [ 11 ] and Ménard et al [ 7 ] who showed that sighted speakers primarily used their lips to produce clear speech while blind speakers prioritized the use of their tongue. Thus access to the visual channel affects control of the speech articulators, and consequently the related acoustic targets.…”
Section: Introductionsupporting
confidence: 89%
“…In a series of studies that investigated the role of vision on the control of speech, it was previously established that congenitally blind speakers use acoustic and articulatory strategies that are significantly different from those of their sighted peers [ 5 – 8 ]. At the acoustic level, it has been shown that blind individuals produced significantly longer vowels than their sighted peers [ 6 , 7 , 9 ] and that sighted speakers produced vowels that were spaced further apart in the vowel space compared to congenitally blind speakers [ 6 ]. At the articulatory level, these authors demonstrate that blind speakers produced significantly smaller lip rounding than sighted speakers.…”
Section: Introductionmentioning
confidence: 99%
“…These indices have been used in a number of studies of child and adult speech to characterise tongue shape for consonants and vowels (e.g. Klein et al, 2013;Ménard et al, 2016;Noiray et al, 2013;Zharkova et al, 2015a). Combining the two measures, such as in Klein et al (2013), may be helpful, as this may provide more complete information on the articulatory mechanisms responsible for producing certain tongue shapes.…”
Section: Analysis Of Ultrasound Data Recorded Without Head-to-transdumentioning
confidence: 98%
“…As Vatikiotis-Bateson et al (1996a, p. 221) put it, "[t]he motor planning and execution associated with producing speech necessarily generates visual information as a by-product." Perhaps more than a by-product, the visual information produced during speech may be integrated fundamentally into our representations of speech, as evidenced by the observation that blind and sighted speakers use different lip movements to produce the same speech sounds (Ménard et al 2016). Sumby & Pollack's (1954) enhancement work, while groundbreaking, did not investigate what aspects of the visual signal were useful to perceivers and why, nor did they speculate about what the mechanism might be that allows perceivers to use this information.…”
Section: Introductionmentioning
confidence: 99%